Study of Coastal Mangrove Conservation in the World - Kristian, Aaron; Oktorie, Olivia (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
Coastal areas are the crucial interface between the two major elements that cover our planet. They provide ground for various ecosystems and biodiversity. In developing countries, many coastal communities live in close vicinity of these areas and rely on the resources of marine and coastal ecosystems to secure food and income. Ecosystems close to shore are however greatly under pressure from varying economic interests and development needs. A common approach to mangrove conservation, as with conservation of many ecosystems, involves establishing protected areas that reduce anthropogenic pressures.